2014
DOI: 10.14348/molcells.2014.0023
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-23b Enhances the Autologous Therapeutic Potential for Degenerative Arthritis by Targeting PRKACB in Synovial Fluid-Derived Mesenchymal Stem Cells from Patients

Abstract: The use of synovial fluid-derived mesenchymal stem cells (SFMSCs) obtained from patients with degenerative arthropathy may serve as an alternative therapeutic strategy in osteoarthritis (OA) and rheumatoid arthritis (RA). For treatment of OA and RA patients, autologous transplantation of differentiated MSCs has several beneficial effects for cartilage regeneration including immunomodulatory activity. In this study, we induced chondrogenic differentiation of SFMSCs by inhibiting protein kinase A (PKA) with a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The SF‐derived mesenchymal stem cells (SFMSCs) collected from degenerative arthropathy patients may serve as an alternative therapeutic approach for RA and OA patients. However, upregulation of miR‐23b may further increase the autologous therapeutic potentiality in SFMSCs from RA patients . Previous study has suggested that Cyr61, fibroblast‐like synoviocytes (FLS) secreted ECM protein, promotes the proliferation of FLS and differentiation of T helper 17 cell .…”
Section: Mirna‐regulated Other Events In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…The SF‐derived mesenchymal stem cells (SFMSCs) collected from degenerative arthropathy patients may serve as an alternative therapeutic approach for RA and OA patients. However, upregulation of miR‐23b may further increase the autologous therapeutic potentiality in SFMSCs from RA patients . Previous study has suggested that Cyr61, fibroblast‐like synoviocytes (FLS) secreted ECM protein, promotes the proliferation of FLS and differentiation of T helper 17 cell .…”
Section: Mirna‐regulated Other Events In Ramentioning
confidence: 99%
“…However, upregulation of miR-23b may further increase the autologous therapeutic potentiality in SFMSCs from RA patients. 71 Previous study has suggested that Cyr61, fibroblast-like synoviocytes (FLS) secreted ECM protein, promotes the proliferation of FLS and differentiation of T helper 17 cell. 72 Study observed that miR-22…”
Section: B Mirnas Regulation Of Synovial Tissue and Cellsmentioning
confidence: 99%
“…Certain miRNAs regulate the level of MMPs indirectly through targeting other molecules. For example, miR-23b is important for chondrogenesis by targeting PRKACB and downregulating MMP-9 [111]. Furthermore, p16INK4a accumulates in OA and enhances the mRNA expression of MMP1 and MMP13 [112].…”
Section: Mirnas In Inflammation and Matrix Degradation In Osteoarthritismentioning
confidence: 99%
“…miRNA-23b overexpression induced chondrogenic differentiation by downregulating protein kinase A (PKA) signaling by targeting Prkacb that encodes a catalytic subunit of PKA, in synovial fluid-derived mesenchymal stem cells [51]; miR-23b may contribute to OA progression by inducing chondrocyte differentiation.…”
Section: Role Of Microrna In Articular Cartilage Homeostasis and Ostementioning
confidence: 99%